2022
DOI: 10.51731/cjht.2022.241
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomic Testing in Depression: A 2021 Update

Abstract: An update to a 2020 CADTH Rapid Review was conducted to capture new literature published since 2019 examining the effectiveness of drug treatment informed by genetic testing compared to usual care for adults with depression. Eleven studies were identified: 1 systematic review, 1 health technology assessment, 4 randomized controlled trials reported in 5 publications, 1 non-randomized study, 1 cohort study with historical control, and 2 uncontrolled before-and-after studies. Similar to the conclusions of the 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
(159 reference statements)
0
2
0
Order By: Relevance
“…82 For patients with bipolar disorder, the findings from the meta-analysis (which included a total of 223 participants from 2 studies) indicated that there were no significant differences between treatment guided by pharmacogenomic testing and treatment as usual with respect to efficacy. 82 In addition to these systematic reviews, CADTH previously conducted 2 Rapid Reviews 83,84 on the clinical effectiveness of pharmacogenomic testing for people with depression� Findings of these previous reports suggested that the available evidence was inconclusive because the included studies reported mixed results (i�e�, some studies suggested pharmacogenomic testing improved outcomes while others suggested there was no difference between pharmacogenomic testing and treatment as usual)� 83,84 Additional details on the methodology and findings of these CADTH reports are available in the reports. 83,84 It is important to take into consideration the significant overlap in the primary studies that are included in these reviews when interpreting their findings.…”
Section: Major Depressive Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…82 For patients with bipolar disorder, the findings from the meta-analysis (which included a total of 223 participants from 2 studies) indicated that there were no significant differences between treatment guided by pharmacogenomic testing and treatment as usual with respect to efficacy. 82 In addition to these systematic reviews, CADTH previously conducted 2 Rapid Reviews 83,84 on the clinical effectiveness of pharmacogenomic testing for people with depression� Findings of these previous reports suggested that the available evidence was inconclusive because the included studies reported mixed results (i�e�, some studies suggested pharmacogenomic testing improved outcomes while others suggested there was no difference between pharmacogenomic testing and treatment as usual)� 83,84 Additional details on the methodology and findings of these CADTH reports are available in the reports. 83,84 It is important to take into consideration the significant overlap in the primary studies that are included in these reviews when interpreting their findings.…”
Section: Major Depressive Disordermentioning
confidence: 99%
“…82 In addition to these systematic reviews, CADTH previously conducted 2 Rapid Reviews 83,84 on the clinical effectiveness of pharmacogenomic testing for people with depression� Findings of these previous reports suggested that the available evidence was inconclusive because the included studies reported mixed results (i�e�, some studies suggested pharmacogenomic testing improved outcomes while others suggested there was no difference between pharmacogenomic testing and treatment as usual)� 83,84 Additional details on the methodology and findings of these CADTH reports are available in the reports. 83,84 It is important to take into consideration the significant overlap in the primary studies that are included in these reviews when interpreting their findings. The inclusion of data from primary studies across multiple evidence syntheses could cause double counting of data from the same primary studies, leading to a biased interpretation of the results�…”
Section: Major Depressive Disordermentioning
confidence: 99%